2017
DOI: 10.1186/s13047-016-0185-y
|View full text |Cite
|
Sign up to set email alerts
|

Exploring musculoskeletal injuries in the podiatry profession: an international cross sectional study

Abstract: BackgroundWorkplace injury is an international costly burden. Health care workers are an essential component to managing musculoskeletal disorders, however in doing this, they may increase their own susceptibility. While there is substantial evidence about work-related musculoskeletal disorders across the health workforce, understanding risk factors in specific occupational groups, such as podiatry, is limited.The primary aim of this study was to determine the prevalence and intensity of work related low back … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 23 publications
1
11
1
Order By: Relevance
“…Musculoskeletal pain has been reported as a major problem among other health care professions whose tasks require adoption of flexed postures including dentists and podiatrists . Previous studies using self‐reported data found LBP in surgeons to be far higher than what was found within these participants within this present study.…”
Section: Discussioncontrasting
confidence: 56%
“…Musculoskeletal pain has been reported as a major problem among other health care professions whose tasks require adoption of flexed postures including dentists and podiatrists . Previous studies using self‐reported data found LBP in surgeons to be far higher than what was found within these participants within this present study.…”
Section: Discussioncontrasting
confidence: 56%
“…Numerous studies have shown that prevalence and incidence of musculoskeletal injuries in different parts of the body are higher in dentists compared with other professions. The prevalence of these complaints in different studies throughout the world has been reported as 63–93% in waist, neck, shoulder, and hands [17] , [18] , [19] , [20] , [21] .…”
Section: Introductionmentioning
confidence: 99%
“…Four themes related to musculoskeletal pain emerged: (a) organizational and procedural responses to injury, (b) giving up work, taking time off, reducing hours, (c) maintaining good musculoskeletal health, and (d) environmental change. These studies demonstrate the effectiveness of evidence-based ergonomics methods integrated into the healthcare workplace to address the prevalence of musculoskeletal injuries and disorders among workers(Cheng et al, 2016;Williams et al, 2017).…”
mentioning
confidence: 72%
“…Cheng et al, 2016). Likewise,Williams et al (2017) argued that there is a need for policies within healthcare facilities to consider how to mitigate healthcare professionals' musculoskeletal health. The role of staff in providing healthcare makes them susceptible to musculoskeletal health (Williams et al, 2017).…”
mentioning
confidence: 99%